2019
DOI: 10.5194/acp-19-10865-2019
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the composition of organic compounds ( ≥  C6) in PM2.5 in wintertime in Beijing, China

Abstract: Abstract. Organic matter is a major component of PM2.5 in megacities. In order to understand the detailed characteristics of organic compounds (≥ C6) at a molecular level on non-haze and haze days, we determined more than 300 organic compounds in the PM2.5 from an urban area of Beijing collected in November–December 2016 using two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC × GC-ToF-MS). The identified organic compounds have been classified into groups, and quantitative metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…This selectivity of adsorption suggests that molecules with planar structures could form more stable and larger aggregates when interacting with BC in atmosphere. This is in keeping with previously reported correlations between the concentrations of aromatic compounds and aerosol PM, notably those of polycyclic aromatic hydrocarbons (PAHs) which could have been formed from small aromatic molecules (Haritash and Kaushik, 2009;Mu et al, 2017;Lyu et al, 2019;Richter and Howard, 2000;Marr et al, 2006;Elzein et al, 2019;Lv et al, 2016;Polidori et al, 2008).…”
Section: Methodssupporting
confidence: 92%
“…This selectivity of adsorption suggests that molecules with planar structures could form more stable and larger aggregates when interacting with BC in atmosphere. This is in keeping with previously reported correlations between the concentrations of aromatic compounds and aerosol PM, notably those of polycyclic aromatic hydrocarbons (PAHs) which could have been formed from small aromatic molecules (Haritash and Kaushik, 2009;Mu et al, 2017;Lyu et al, 2019;Richter and Howard, 2000;Marr et al, 2006;Elzein et al, 2019;Lv et al, 2016;Polidori et al, 2008).…”
Section: Methodssupporting
confidence: 92%
“…As a result, air pollutants in haze events in the NCP are rapidly transported to downwind regions such as the YRD (Kang et al, 2019) or East China Sea (F. Wang et al, 2016). To date, most of studies have focused on physicochemical characteristics of aerosol particles and regional haze formation in the NCP or the YRD as two isolated regions (Cheng et al, 2013;Ge et al, 2018;Herrmann et al, 2014;Lyu et al, 2019;Wang, An, et al, 2014;S. Zhai et al, 2018).…”
mentioning
confidence: 99%
“…This unusually low concentration compared to the cited studies might be due to the fact that our campaign was conducted earlier in summer than the others. Studies have also shown that the formation rate of SO 2− 4 is particularly high during haze episodes, with a strong contribution from heterogeneous oxidation within haze droplets (Ma et al, 2018;Wang et al, S. S. Steimer et al: Differences in the composition of organic aerosols in Beijing 2006), leading to high maximum concentrations of sulfate during haze events, of which several strong ones occurred in winter during our campaign. While organosulfate formation has been primarily understood to be a secondary process, a recent direct-infusion UHRMS study of coal combustion by Song et al (2019) found 5 %-25 % of formulae in the methanol-extracted fraction to contain sulfur, indicating the potential importance of direct organosulfate emissions.…”
Section: Sulfur-and Nitrogen-containing Compoundsmentioning
confidence: 56%